Kajian Penggunaan Bakteri Bacillus subtilis dalam Penanganan Tumpahan Minyak Mentah - Kusdini, Kusdini; Kastilon, Kastilon; Rokky Gumanti; Reflis, Reflis; Satria P Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
The global demand for energy is driving increased exploration, production and processing of crude oil, increasing the risk of oil spills during these processes and contaminating marine habitats and biota. As hazardous and toxic substances, oil spills require effective and comprehensive management. Bioremediation uses the metabolism of microbes to break down hydrocarbons and convert contaminants into harmless compounds. One species of hydrocarbon-degrading bacteria suitable for bioremediation is Bacillus subtilis. Its adaptability to changes in temperature, salinity, and oxygen levels, as well as its resistance to environmental stress, make it an ideal choice for bioremediation as a sustainable and efficient solution to oil pollution in marine ecosystems. This study aims to explore the potential use of Bacillus subtilis as an alternative for managing crude oil spills, particularly in Indonesian waters.